Bacteroides fragilis Prevents Clostridium difficile Infection in a Mouse Model by Restoring Gut Barrier and Microbiome Regulation - Deng, Huimin; Yang, Siqi; Zhang, Yucheng; Qian, Kai; Zhang, Zhaohui; Liu, Yangyang; Wang, Ye; Bai, Yang; Fan, Hongying; Zhao, Xinmei; Zhi, Fachao (Frontiers in Microbiology, 2018)
Clostridium difficile is currently the leading cause of nosocomial infection. Antibiotics remain the first-line therapy for C. difficile-associated diseases (CDAD), despite the risks of resistance promotion and further gut microbiota perturbation. Notably, the abundance of Bacteroides fragilis was reported to be significantly decreased in CDAD patients. This study aimed to clarify the prophylactic effects of B. fragilis strain ZY-312 in a mouse model of C. difficile infection (CDI). The CDI mouse model was successfully created using C. difficile strain VPI 10463 spores, as confirmed by lethal diarrhea (12.5% survival rate), serious gut barrier disruption, and microbiota disruption. CDI model mice prophylactically treated with B. fragilis exhibited significantly higher survival rates (100% in low dosage group, 87.5% in high dosage group) and improved clinical manifestations. Histopathological analysis of colon and cecum tissue samples revealed an intact gut barrier with strong ZO-1 and Muc-2 expression. The bacterial diversity and relative abundance of gut microbiota were significantly improved. Interestingly, the relative abundance of Akkermansia muciniphila was positively correlated with B. fragilis treatment. In vitro experiments showed that B. fragilis inhibited C. difficile adherence, and attenuated the decrease in CDI-induced transepithelial electrical resistance, ZO-1 and MUC-2 loss, and apoptosis, suggesting that B. fragilis protected against CDI possibly by resisting pathogen colonization and improving gut barrier integrity and functions. In summary, B. fragilis exerted protective effects on a CDI mouse model by modulating gut microbiota and alleviating barrier destruction, thereby relieving epithelial stress and pathogenic colitis triggered by C. difficile. This study provides an alternative preventative measure for CDI and lays the foundations for further investigations of the relationships among opportunistic pathogens, commensal microbiota, and the gut barrier.